Primary central nervous system histiocytic sarcoma: A case report and review of literature. Issue 26 (June 2018) - Ma, Shuang; Schild, Michael; Tran, Diana; Zhang, Xuefeng; Zhang, Wan-Lin; Shen, Shuai; Xu, Hong-Tao; Yang, Lian-He; Wang, Endi
Abstract: Rationale: Primary central nervous system histiocytic sarcoma (PCNSHS) is a rare lymphohematopoietic tumor with a histiocytic cell origin. To our knowledge, only 28 cases have been published in English and 2 cases in Chinese. Patient concerns: A 49-year-old Asian female presented to the hospital with a 2 month history of hypomnesia, odynophagia, and gait disorder. Physical examination demonstrated decreased lower extremity muscle strength. The patient denied a history of malignancy. Diagnoses: Radiology demonstrated a lesion in parietal lobe with uniformenhancement. Histologic analysis showed pleomorphic tumor cells with a loose arrangement, effacing the normal brain tissue. The tumor cells exhibited abundant eosinophilic cytoplasm, highly atypical nuclei and predominant nucleoli. Immunohistochemistry revealed positive immunoreactivity for CD45, lysozyme, CD68, and CD163, and negative for pan-cytokeratin (CK), epithelial membrane antigen (EMA), glial fibrillary acidic protein (GFAP), CD3, CD20, CD1a, CD79a, CD138, oligodendrocyte transcription factor (olig2), CD15, melan-A, CD30, CD21, CD35, Human Melanoma Black-45 (HMB45), and anaplastic lymphoma kinase-1 (ALK-1). The diagnosis of PCNSHS was rendered. Interventions: The patient underwent complete surgical resection and adjuvant radiotherapy. Outcomes: Follow-up information shows the patient died 8 months following the initial diagnosis. Lessons: PCNSHS is extremely rare with an aggressive clinical course. Immunohistiochemistry is necessary to make this diagnosis and to exclude other primary intracranial and lymphohematopoietic tumors. Further research is required to improve the outcome of patients with PCNSHS.